The problem of paramedicine in Poland – from the ethical point of view - Sytnik-Czetwertyński, Janusz; Skowron, Adam; Ostrowski, Janusz; Pinkas, Jarosław (Wiedza Medyczna, 2022)
The aim of this article is to analyze the concept of "paramedicine" and to present it in a mainly ethical aspect. The problem will be considered mainly in the context of Poland and Polish legal regulations. After an attempt to define what paramedicine is, an ethical and legal analysis of the problem follows. The whole article ends with conclusions.